2021
DOI: 10.1103/physrevlett.126.233404
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Many-Body Dynamics Near a Conical Intersection with Trapped Rydberg Ions

Abstract: Conical intersections between electronic potential energy surfaces are paradigmatic for the study of nonadiabatic processes in the excited states of large molecules. However, since the corresponding dynamics occurs on a femtosecond timescale, their investigation remains challenging and requires ultrafast spectroscopy techniques. We demonstrate that trapped Rydberg ions are a platform to engineer conical intersections and to simulate their ensuing dynamics on larger length and time scales of the order of nanome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 53 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Most of these quantum simulations have been performed in reciprocal space to simulate solid-state systems, including geometric phases around Dirac points [3,32,33]. Theoretical proposals for simulating molecular conical intersections have included using trapped Rydberg ions to simulate electronic populations [34], circuit quantum electrodynamics to simulate emission spectra [35], and cavity quantum electrodynamics to simulate collapse-revival characteristics of a spreading wavepacket [36]. To date, the only experimental quantum simulation of a chemical conical intersection demonstrated branching between different photochemical reaction products with strong dissipation [37].…”
mentioning
confidence: 99%
“…Most of these quantum simulations have been performed in reciprocal space to simulate solid-state systems, including geometric phases around Dirac points [3,32,33]. Theoretical proposals for simulating molecular conical intersections have included using trapped Rydberg ions to simulate electronic populations [34], circuit quantum electrodynamics to simulate emission spectra [35], and cavity quantum electrodynamics to simulate collapse-revival characteristics of a spreading wavepacket [36]. To date, the only experimental quantum simulation of a chemical conical intersection demonstrated branching between different photochemical reaction products with strong dissipation [37].…”
mentioning
confidence: 99%
“…Recently, the Rydberg trapped ion realization of the Jahn-Teller modes was proposed in Reference [20].…”
Section: Periodic Modulating Dissipative Jahn-teller Interactionmentioning
confidence: 99%
“…It has been shown that RAB can be used to limit the blockade error [40], and to construct the multiple qubit Toffoli and Fan-out gates in a fast way [41]. Recently, it has been shown that non-adiabatic dynamics around a conical intersection can be studied under the RAB condition with trapped Rydberg ions [42].…”
Section: Introductionmentioning
confidence: 99%